Capabilities as Real Options - Kogut, Bruce; Kulatilaka, Nalin (Organization Science, 2001)
Strategy research consists of a balance between positive and normative theory. Normative theories suggest particular heuristics, or cognitive representations, to find appropriate solutions. Heuristics permit faster solutions to real-time problems; they also suffer from the potential of negative transfer to inappropriate applications. The theory of real options provides the appropriate heuristic framing of competencies and exploratory search. A real options approach marries the theory of financial options to foundational ideas in strategy, organizational theory, and complex systems. We join these approaches to identify three pairs of concepts: scarce factor and the underlying asset in option theory, inertia and irreversibility, and the ruggedness of landscape and option values. Strategic theories of resources largely define a core competence as unique and nonimmutable. In doing so, this definition has wrongly forgotten Barney's initial insight into scarce factor markets as determining the valuation of a competitive asset. Financial theory of real options derives its heuristics of investing in exploratory search by inferring future value of today's investments from market prices. We apply the three conceptual pairs to the evaluation of capabilities as real options through a formal descriptive model. The valuation of core capabilities is derived from observing the price dynamics of correlated strategic factors in the market. Because of inertia, managers cannot easily adjust the wrong set of organizational capabilities to the emergence of market opportunities. However, firms that have made investments in capabilities appropriate to these opportunities are able to respond. From this description, we define core competence as the choice of capabilities that permits the firm to make the best response to market opportunities. The heuristic framing of capabilities as real options guides the normative evaluation of the balance between exploitation and exploration.